2018
DOI: 10.1093/ejcts/ezy172
|View full text |Cite
|
Sign up to set email alerts
|

Association between the severity of acquired von Willebrand syndrome and gastrointestinal bleeding after continuous-flow left ventricular assist device implantation

Abstract: UMIN000018135.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 19 publications
1
43
1
Order By: Relevance
“…It designates as a hemostatic disorder the acquired von Willebrand syndrome (AVWS) 4) . AVWS also occurs in other conditions requiring left ventricular assist device implantation 8) .…”
Section: Discussionmentioning
confidence: 99%
“…It designates as a hemostatic disorder the acquired von Willebrand syndrome (AVWS) 4) . AVWS also occurs in other conditions requiring left ventricular assist device implantation 8) .…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, superficial SSI was observed at the umbilicus incision, yet did not spread to the site of the driveline or pump pocket due to early drainage and washing. With regard to bleeding complications, it is known that LVADs induce acquired von Willebrand syndrome [12,13]. Therefore, surgeons need to be aware that the patients with LVADs tend to bleed even after anti-coagulation therapy is stopped.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the gastrointestinal bleeding that develops at a later phase is considered to be from gastrointestinal angiodysplasia, since it would take some time, possibly several months, for the angiodysplasia to form after LVAD implantation. We have recently demonstrated that all 41 examined LVAD-treated patients exhibited far more severe AVWS compared to that in patients with aortic stenosis by quantitative analysis of AVWS 96) . Twelve patients (approximately 30%) developed gastrointestinal bleeding, where bleeding frequently occurred in patients with a VWF large multimer index below 40% 96) , suggesting a critical role of AVWS in gastrointestinal bleeding in patients treated with LVAD.…”
Section: Avws Caused By Mechanical Circulatory Supportmentioning
confidence: 98%
“…We have recently demonstrated that all 41 examined LVAD-treated patients exhibited far more severe AVWS compared to that in patients with aortic stenosis by quantitative analysis of AVWS 96) . Twelve patients (approximately 30%) developed gastrointestinal bleeding, where bleeding frequently occurred in patients with a VWF large multimer index below 40% 96) , suggesting a critical role of AVWS in gastrointestinal bleeding in patients treated with LVAD. It is noted that four cases developed bleeding within 40 days after LVAD implantation, with 8 cases after 142 days 96) .…”
Section: Avws Caused By Mechanical Circulatory Supportmentioning
confidence: 98%